2015
DOI: 10.1002/asna.201512239
|View full text |Cite
|
Sign up to set email alerts
|

The effects of superhigh magnetic fields on the equations of state of neutron stars

Abstract: By introducing Dirac's δ-function in superhigh magnetic fields, we deduce a general formula for the pressure of degenerate and relativistic electrons, P e , which is suitable for superhigh magnetic fields, discuss the quantization of Landau levels of electrons, and consider the quantum electrodynamic(QED) effects on the equations of states (EOSs) for different matter systems. The main conclusions are as follows: the stronger the magnetic field strength, the higher the electron pressure becomes; compared with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 27 publications
2
42
1
Order By: Relevance
“…Over the years, it has been shown that the presence of strong magnetic fields significantly affects the energy levels of charged particles due to Landau quantization. These effects have been taken into account in the EoS of models in order to describe hyperon stars (Chakrabarty et al 1997;Broderick et al 2000Broderick et al , 2002Lopes & Menezes 2012;Sinha et al 2013;Casali et al 2014;Gomes et al 2014;Gao et al 2015), quark stars (Perez Martinez et al 2008;Felipe et al 2011;Orsaria et al 2011;Paulucci et al 2011;Denke & Pinto 2013;Dexheimer et al 2014;Isayev 2015), hybrid stars (Rabhi et al 2009;Dexheimer et al 2012Dexheimer et al , 2013, and stars with meson condensates Schramm et al (2015). The effects of the anomalous magnetic moment (AMM) were also investigated through the corresponding coupling of the baryons to the electromagnetic field tensor (see Canuto & Chiu 1968a;Broderick et al 2000Broderick et al , 2002Strickland et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, it has been shown that the presence of strong magnetic fields significantly affects the energy levels of charged particles due to Landau quantization. These effects have been taken into account in the EoS of models in order to describe hyperon stars (Chakrabarty et al 1997;Broderick et al 2000Broderick et al , 2002Lopes & Menezes 2012;Sinha et al 2013;Casali et al 2014;Gomes et al 2014;Gao et al 2015), quark stars (Perez Martinez et al 2008;Felipe et al 2011;Orsaria et al 2011;Paulucci et al 2011;Denke & Pinto 2013;Dexheimer et al 2014;Isayev 2015), hybrid stars (Rabhi et al 2009;Dexheimer et al 2012Dexheimer et al , 2013, and stars with meson condensates Schramm et al (2015). The effects of the anomalous magnetic moment (AMM) were also investigated through the corresponding coupling of the baryons to the electromagnetic field tensor (see Canuto & Chiu 1968a;Broderick et al 2000Broderick et al , 2002Strickland et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…S GT + is the total amount of the GT strength available for an initial state given by summing over a complete set a final states in GT transition matrix elements |M GT | 2 i f . The strength distribution is given by [4] (24) which is related to R A (τ ) by a Laplace transform, R A (τ ) = ∞ −∞ S A (E)e −τ E dE. Note that here E is the energy transfer within the parent nucleus, and the strength distribution S GT + (E) has units of MeV −1 .…”
Section: The Smmc Methods and Gamow-teller Response Functionsmentioning
confidence: 99%
“…Some interesting behaviors such as a wide array of X-ray activity including short bursts, large outbursts, giant flares, quasiperiodic oscillations, enhanced spin-down, glitches and antiglitches are displayed in magnetars and discussed by Kaspi and Beloborodov [23]. The electron Fermi energy, and the a e-mail: liujingjing68@126.com electron fraction in SMFs and the dipole magnetic field and spin-down evolutions were explored in detail by Gao et al [24][25][26][27][28] and Zhu et al [29].…”
Section: Introductionmentioning
confidence: 99%
“…They combined IVFSS with IVFS and soft sets, which is the consequence of Yang et al [19] Sabir Hussain [15] worked on soft expert topological spaces, Shabir, M and Naz, M [16] on soft topological spaces, Wand Y.J and Lee [18] worked on generalized TOPSIS for fuzzy multiple criteria group decision making. Gao [5][6], Ramik [14], Dodd [3], Hwang [7] and Linkov [10] works further on decision making problems.…”
Section: Introductionmentioning
confidence: 99%